2021
DOI: 10.1186/s13054-021-03518-4
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of respiratory system compliance in mechanically ventilated covid-19 patients

Abstract: Background Heterogeneous respiratory system static compliance (CRS) values and levels of hypoxemia in patients with novel coronavirus disease (COVID-19) requiring mechanical ventilation have been reported in previous small-case series or studies conducted at a national level. Methods We designed a retrospective observational cohort study with rapid data gathering from the international COVID-19 Critical Care Consortium study to comprehensively desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…It is difficult to directly compare this improvement in oxygenation with other reports because many studies have not addressed the time of P/F measurement. However, in two recent reports, the P/F ratio in patients with COVID-19-related ARDS in the first 48 hours was reported to be 113 mmHg 16 and 107 mmHg, 17 which are both very similar to the P/F ratio on day 1 in our study (107 mmHg).…”
Section: Discussionsupporting
confidence: 86%
“…It is difficult to directly compare this improvement in oxygenation with other reports because many studies have not addressed the time of P/F measurement. However, in two recent reports, the P/F ratio in patients with COVID-19-related ARDS in the first 48 hours was reported to be 113 mmHg 16 and 107 mmHg, 17 which are both very similar to the P/F ratio on day 1 in our study (107 mmHg).…”
Section: Discussionsupporting
confidence: 86%
“…Among the other time-independent factors, only baseline PEEP was found to reduce mortality hazards in our analyses, in contrast with previous evidence associating higher PEEP with mortality ( 21 ). These findings emphasize the challenges in setting the optimal PEEP in COVID-19 patients ( 26 ), particularly in light of early controversial reports on heterogeneous static respiratory system compliance in infected patients ( 27 ). Nevertheless, potential dissimilarities in ventilatory management across different geographical regions should be considered to cautiously infer from these results.…”
Section: Discussionmentioning
confidence: 56%
“…The effect of a different predicted FRC could explain the findings of Li Bassi et al [ 26 ] who found, in their analysis on COVID-19 ARDS patients, a lower C rs in female patients: on average, females have a smaller stature than males, and this predicts lower FRC. Moreover, female sex by itself gives a lower predicted FRC than male sex for the same height and age, whereas BMI, which was higher for female patients in Li Bassi’s cohort, has an inverse relationship with predicted FRC.…”
Section: Discussionmentioning
confidence: 85%